2019
DOI: 10.1039/c9ob01781j
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of APOBEC3 enzymes by single-stranded DNAs containing 2′-deoxyzebularine

Abstract: Selective inhibitors for APOBEC3B and APOBEC3A/G were obtained by substituting the preferred 2′-deoxycytidine by 2′-deoxyzebularine (Z) in a CCC DNA-motif.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 55 publications
6
50
1
1
Order By: Relevance
“…Our results also highlight the importance of protonation of the N3 atom in dZ for its inhibitory behaviour. Noteworthy differences in inhibition profiles among different A3 enzymes observed here point to possibilities of obtaining highly specific A3 inhibitors, thereby supporting our approach to development of oligonucleotide‐based A3 inhibitors with the aid of chemically modified nucleosides, the structures of which can stall enzymatic cytosine deamination . Future work will continue to focus on the chemical optimisation of our ssDNA‐based A3 inhibitors and their evaluation in vitro and in vivo.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Our results also highlight the importance of protonation of the N3 atom in dZ for its inhibitory behaviour. Noteworthy differences in inhibition profiles among different A3 enzymes observed here point to possibilities of obtaining highly specific A3 inhibitors, thereby supporting our approach to development of oligonucleotide‐based A3 inhibitors with the aid of chemically modified nucleosides, the structures of which can stall enzymatic cytosine deamination . Future work will continue to focus on the chemical optimisation of our ssDNA‐based A3 inhibitors and their evaluation in vitro and in vivo.…”
Section: Resultssupporting
confidence: 60%
“…Noteworthy differences in inhibition profiles among different A3 enzymes observed here point to possibilities of obtaining highly specific A3 inhibitors, thereby supporting our approach to development of oligonucleotide-based A3 inhibitors with the aid of chemically modified nucleosides, the structures of which can stall enzymatic cytosine deamination. [36] Future work will continue to focus on the chemical optimisation of our ssDNA-based A3 inhibitors and their evaluation in vitro and in vivo. Nucleotides flanking the target dZ and 5FdZ motifs can be further modified to improve inhibitory potential and to enhance the lifetimes of oligonucleotides in biological media.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the position of the SEC elution profile, we conclude that peak 1 corresponds to homo-dimeric A3BCTD* (with a molecular weight of ~44 kDa, referred to as 'A3BCTD* dimer'). This contrasts with the other A3BCTD variants we reported in previous studies [59,61,80], A3BCTD-QM-ΔL3, A3BCTD-QM-ΔL3-E255A, and A3BCTD-DM, which eluted only as monomeric species. Previous reports have suggested that A3A exists as both a monomer and a dimer in vitro [52,53].…”
Section: Multimerization Of A3bctd* In Solutioncontrasting
confidence: 99%
“…The catalytically active A3BCTD* was expressed and purified as described previously [59,61,62]. This variant contained four substitution mutations (F200S, W228S, L230K, F308K), the truncation of loop 3, and the transplant of loop 1 from A3A.…”
Section: Protein Expression and Purification Of A3bctd* Proteinmentioning
confidence: 99%
See 1 more Smart Citation